A new species of Scandarma (Crustacea: Brachyura: Sesarmidae) from Sabah, Borneo, Malaysia - Ng, Peter K.l. (Zootaxa, 2013)
A new species of terrestrial sesarmid crab, Scandarma raymondi, is described from Sabah, Malaysia. This is the third spe-cies in the genus; others are from Taiwan, Japan and Sarawak, Borneo. The new species differs from congeners in the live coloration, proportions of the carapace and ambulatory legs and morphologies of the male abdomen, chela and male first gonopod.